2019
DOI: 10.1021/acsanm.9b01714
|View full text |Cite
|
Sign up to set email alerts
|

Confinement Effects and Charge Dynamics in Zn3N2 Colloidal Quantum Dots: Implications for QD-LED Displays

Abstract: Zinc nitride (Zn 3 N 2 ) colloidal quantum dots are composed of nontoxic, low-cost, and earth-abundant elements. The effects of quantum confinement on the optical properties and charge dynamics of these dots are studied using steady-state optical characterization and ultrafast fluencedependent transient absorption. The absorption and emission energies are observed to be size-tunable, with the optical band gap increasing from 1.5 to 3.2 eV as the dot diameter decreased from 8.9 to 2.7 nm. Size-dependent absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
(68 reference statements)
2
11
0
Order By: Relevance
“…For further understanding the effect of NaCl confinement on the luminescence properties of Au NCs, the absolute QYs of the GSH-Au NCs solution and GSH-Au NCs/NaCl crystal were measured, respectively. The absolute QY of GSH-Au NCs solution was determined to be 1%, which is consistent with previous reports. , Amazingly, the GSH-Au NCs/NaCl crystal exhibited a much improved absolute QY of 30%. The 30-fold enhancement in QY revealed that NaCl confinement can significantly modify the emission of GSH-Au NCs.…”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For further understanding the effect of NaCl confinement on the luminescence properties of Au NCs, the absolute QYs of the GSH-Au NCs solution and GSH-Au NCs/NaCl crystal were measured, respectively. The absolute QY of GSH-Au NCs solution was determined to be 1%, which is consistent with previous reports. , Amazingly, the GSH-Au NCs/NaCl crystal exhibited a much improved absolute QY of 30%. The 30-fold enhancement in QY revealed that NaCl confinement can significantly modify the emission of GSH-Au NCs.…”
Section: Results and Discussionsupporting
confidence: 91%
“…To date, numerous studies have explored the potential application of thiolate-capped Au NCs in sensing, bioimaging, and lighting. In particular, the Au NCs have been recognized as one of the most attractive materials for designing white light-emitting devices (WLEDs). However, compared with conventional phosphors for WLEDs (such as semiconductor quantum dots, organic fluorophores, and rare earth phosphors, thiolate-protected Au NCs have a much lower luminescence quantum yield (QY, ∼1%) . Moreover, the luminescence emission of thiolate-protected Au NCs usually decreases severely under upper ambient temperature, continuous UV irradiation, and long-term preservation. The low QY and poor stability of thiolate-protected Au NCs greatly limit their application in WLEDs and many other fields.…”
Section: Introductionmentioning
confidence: 99%
“…These PL lifetimes are the same order of magnitude as GaN and Zn 3 N 2 nanocrystals made by other methods. [ 10b,15 ]…”
Section: Resultsmentioning
confidence: 99%
“…The band gap of Zn 3 N 2 is still debatable in the concept of narrow or wide band gap and direct or indirect bandgap, where it needs lot of theoretical understanding. Very few literature studies have reported on the optical properties of Zn 3 N 2 , , focusing further toward optoelectronic applications. The biological applications of Zn 3 N 2 are not yet examined similar to other inorganic nanoparticles such as gold, silver, CdS, CdSe and so forth.…”
Section: Introductionmentioning
confidence: 99%